2021
DOI: 10.32098/mltj.04.2021.18
|View full text |Cite
|
Sign up to set email alerts
|

Radial versus Combined Shockwave Therapy in the Management of Proximal Hamstring Tendinopathy: Similar Functional Outcomes in Running Cohort

Abstract: Background. Proximal hamstring tendinopathy is a common cause of gluteal pain. Extracorporeal shockwave therapy may be an effective treatment in proximal hamstring tendinopathy. However, published outcomes are primarily limited to evaluating radial shockwave, and the use of combined treatment (focus and radial treatment) and outcomes for management in runners are not well described. The purpose of this report was to characterize functional outcomes using radial and combined shockwave in the management of proxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…One case series showed that 22 of 32 runners with proximal hamstring tendinopathy and 3 of 4 runners with distal/mid-hamstring tendinopathy met MCID after ESWT treatment 45. Another case series with some overlapping participants with Mitchkash et al 45 demonstrated that both R-SWT and combined ESWT (focused and radial) resulted in similar gains in VISA-Hamstring in management of proximal hamstring tendinopathy 65. Two case reports described an elite female para swimming athlete with bilateral hamstring pain66 and a female ultramarathon runner67 successfully returning to sport following ESWT.…”
Section: Resultsmentioning
confidence: 99%
“…One case series showed that 22 of 32 runners with proximal hamstring tendinopathy and 3 of 4 runners with distal/mid-hamstring tendinopathy met MCID after ESWT treatment 45. Another case series with some overlapping participants with Mitchkash et al 45 demonstrated that both R-SWT and combined ESWT (focused and radial) resulted in similar gains in VISA-Hamstring in management of proximal hamstring tendinopathy 65. Two case reports described an elite female para swimming athlete with bilateral hamstring pain66 and a female ultramarathon runner67 successfully returning to sport following ESWT.…”
Section: Resultsmentioning
confidence: 99%
“…Other variables that warrant further investigation that may have affected clinical outcomes include load intensity specificity and tempo with exercise selection. Of the 13 studies, only two studies were specific in their load intensities either by RPE or by the percentage of 1RM [ 6 , 20 ], with six studies lacking specificity of either “moderate/high load” or “progressive” [ 7 , 15 , 16 , 17 , 22 , 35 ], and five studies lacking the reporting of exercise intensity in general [ 5 , 18 , 21 , 23 , 24 ]. Furthermore, of the 13 studies, only two [ 6 , 7 ] commented on loading rates associated with exercise, making it difficult to further analyze differences observed in clinical outcomes across studies.…”
Section: Discussionmentioning
confidence: 99%
“… Summary of risk of bias assessment for non-randomized control trials. Note: Domains: D1: bias due to confounding, D2: bias due to selection of participants, D3: bias in classification of interventions, D4: bias due to deviations from intended interventions, D5: bias due to missing data, D6: bias in measurement of outcomes, D7: bias in selection of the reported result [ 21 , 24 , 25 ]. …”
Section: Figurementioning
confidence: 99%